5-YEAR RELATIVE SURVIVAL RATE BETWEEN SEMINOMA AND NON-SEMINOMA TESTICULAR CANCER IN SINGLE CENTER (Indonesian Journal of Urology, 2023)
ABSTRACT Objective: This study was conducted to provide data about the survival rate of testicular cancer patients with different histology in the year 2013 – 2017 in Adam Malik General Hospital and to compare these estimates with other studies conducted in another center. Material & Methods: Medical records of testicular cancer patients from 2013 to 2017 in Adam Malik General Hospital were collected. We measured 5-year relative survival between the histology group of seminoma and non-seminoma estimated using Kaplan-Meier survival analysis. Also, using Kaplan-Meier for survival analysis estimated, 5-year relative survival between metastatic and non-metastatic was estimated. Results: 63 male patients (mean age 27.5 ± 17.6 years old) were included in this study. The distribution of histology were non-seminoma (53.9%), seminoma (39.9%), non-Hodgkin lymphoma (4.7%), and gonadoblastoma (1.5%). The 5-year relative survival rate was 82.5% for the seminoma group and 80.9 % for the non-seminoma group. The 5-year survival rate in the seminoma group with metastatic was 77.8% and in the non-metastatic group was 87.3 %. The 5-year survival rate in the non-seminoma group with metastatic was 74.6 % and in the non-metastatic group was 88.9 %. Conclusion: 5-year relative survival was better for the seminoma group than the non-seminoma group. Moreover, non-metastasis seminoma was found to have a better outcome than the metastatic group. Despite that, in the non-metastatic group, it is found that non-seminoma testicular cancer has a better survival rate than seminoma testicular cancer. Keywords: 5-year relative survival rate, seminoma, non-seminoma, testicular cancer.